Brainwave Self-Regulation During Bispectral IndexTM Neurofeedback in Trauma Center Nurses and Physicians After Receiving Mindfulness Instructions - Dunham, C. Michael; Burger, Amanda L.; Hileman, Barbara M.; Chance, Elisha A.; Hutchinson, Amy E.; Kohli, Chander M.; DeNiro, Lori; Tall, Jill M.; Lisko, Paul (Frontiers in Psychology, 2019)
Fifty-seven level I trauma center nurses/physicians participated in a 4-day intervention to learn relaxed alertness using mindfulness-based instructions and EEG neurofeedback. Neurofeedback was provided by a Bispectral Index™ (BIS) system that continuously displays a BIS value (0-100) on the monitor screen. Reductions in the BIS value indicate that power in a high-frequency band (30-47 Hz) is decreased and power in an intermediate band (11-20 Hz) is increased. A wellbeing tool with 4 positive affect and 7 negative affect items based on a 5-category Likert scale was used. The wellbeing score is the sum of the positive affect items (positive affect score) and the reverse-scored negative affect items (nonstress score). Of functional concern were 4 negative affect items rated as moderately, quite a bit, or extremely in a large percent. Of greater concern were all 4 positive affect items rated as very slightly or none at all, a little, or moderately in over half of the participants. Mean and nadir BIS values were markedly decreased during neurofeedback when compared to baseline values. Post-session relaxation scores were higher than pre-session relaxation scores. Post-session relaxation scores had an inverse relationship with mean and nadir BIS values. Mean and nadir BIS values were inversely associated with NFB cognitive states (i.e., widening the visual field, decreasing effort, attention to space, and relaxed alertness). For all participants, the wellbeing score was higher on day 4 than on day 1. Participants had a higher wellbeing score on day 4 than a larger group of nurses/physicians who did not participate in the BIS neurofeedback trial. Eighty percent of participants demonstrated an improvement in the positive affect or nonstress score on day 4, when compared to day 1; the wellbeing, nonstress, and positive affect scores were substantially higher on day 4 than on day 1. Additionally, for that 80% of participants, the improvements in wellbeing and nonstress were associated with reductions in day 3 BIS values. These findings indicate that trauma center nurses/physicians participating in an EEG neurofeedback trial with mindfulness instructions had improvements in wellbeing.